Study of the Impact of Singing on University Students - Ma, Heting (International Journal of Social Sciences and Public Administration, 2024)
This study focuses on the effects of singing on college students’ psychological, physiological and social interaction abilities. First of all, we learnt about the current situation and theoretical basis of singing influence research at home and abroad through literature review, and came to the results that singing has a positive influence on college students’ emotional regulation, self-confidence enhancement, and teamwork and interpersonal communication abilities. In addition, singing has a positive effect on the cardiovascular system and respiratory system.